2007
DOI: 10.4319/lo.2007.52.5.1853
|View full text |Cite
|
Sign up to set email alerts
|

Topographic shading and wave exposure influence morphology and ecophysiology of Ecklonia radiata (C. Agardh 1817) in Fiordland, New Zealand

Abstract: Patterns in morphology, pigment concentration, and light saturation kinetics of Ecklonia radiata reveal great morphological and physiological variability among individuals from sites spanning strong gradients in topographic shading and wave exposure among the 14 fjords in southwestern New Zealand. Morphology of E. radiata varies from relatively narrow (85 6 4.7 mm) (mean 6 standard error), thick (3.2 6 0.30 mm) blades from the well-illuminated, wave-exposed outer coast sites to wide, undulate (460 6 36.8 mm,) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
84
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(93 citation statements)
references
References 44 publications
7
84
2
Order By: Relevance
“…Rock wall habitats contain a relatively low diversity of suspension feeding invertebrates with brachiopods and tubeworms as dominant space occupiers (Smith 2001, Wing andJack 2012). There are very low densities of macroalgae, and no significant beds of the common kelp Ecklonia radiata (Wing et al 2007). In this study, Long Sound supported dense populations of blue cod, which have increased since the marine reserve was established.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Rock wall habitats contain a relatively low diversity of suspension feeding invertebrates with brachiopods and tubeworms as dominant space occupiers (Smith 2001, Wing andJack 2012). There are very low densities of macroalgae, and no significant beds of the common kelp Ecklonia radiata (Wing et al 2007). In this study, Long Sound supported dense populations of blue cod, which have increased since the marine reserve was established.…”
Section: Discussionmentioning
confidence: 77%
“…Situated in the south west of New Zealand, this system is characterised by strong gradients in environmental conditions, primarily salinity, light and wave exposure, which have a dramatic influence on productivity patterns (Goebel et al 2005, Wing et al 2007, Wing and Leichter 2011. The resultant spatial diversity in basal organic matter sources fuelling food webs can be directly linked to subpopulation structure, growth and fecundity of benthic invertebrates , Jack et al 2009, Wing 2009 and reef fish (Rodgers and Wing 2008, Lawton et al 2010, McLeod et al 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…Commonly employed impact-control studies measure spatial management outcomes by comparing regions that are under different management regimes (no-take reserve, commercial exclusion zones, open fished areas) but that are otherwise comparable, before and after implementation. However the New Zealand fjords are characterized by strong physical environmental gradients containing the extremes of salinity, wave action and irradiance that together influence patterns of pelagic productivity and density of habitatproviding macroalgae along the axis of each fjord (Goebel et al 2005, Wing et al 2007). The resulting gradient in composition of organic matter source pools can be directly linked to diet, sub-population structure, growth and fecundity of reef fish (Wing et al 2012, Beer andWing 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This was clearly proved in the stipe morphology as we found differences in length and diameter. Similarly, kelps show important phenotypic plasticity in response to environmental heterogeneity, such as waveexposure in Ecklonia radiata (Wernberg et al 2003, Wing et al 2007 is also inversely correlated to water temperatures Kremer 1984, 1986). On the other hand, Hernández-Carmona et al (2001) demonstrated that E. arborea, differing from M. pyrifera, maintained high tissue nitrogen content.…”
Section: Discussionmentioning
confidence: 99%